Optimized Purification Processes for Isolation and Modification of Oligosaccharides from Rathi Cow’s Milk - Desh Deepak A. P. Singh Chauhan; Sana Akhtar Usmani; Sarita Chauhan; Ashutosh Singh; Desh Deepak (Biology and Life Sciences Forum, 2025)
Purification and characterization of milk oligosaccharides is a challenging process due to the complexity of the constituent oligosaccharides, which behave differently under various chemical treatment procedures and often lose their structural properties in the process. Rathi cow’s milk is widely used in the Rajasthan region of India for its nutritional and medicinal benefits. Here, we aim to present an optimized method for the purification and analysis of oligosaccharides present in Rathi cow milk. Contrary to the freeze transport methods used earlier, we treated the collected milk with ethanol for preservation, followed by microfiltration, lyophilization, and fractionation on silica gel (60–120 mesh size) column chromatography (CC) coupled with chloroform/methanol-mediated gradient elution. Fractions 31–45 (1.78 g), 71–80 (470 mg), and 106–120 (498 mg) from CC-1 and fractions 26–49 (1.14 g) from CC-2 were analysed for sugar content via the phenol–sulfuric acid method. Fraction homogeneity was confirmed using high-performance liquid chromatography. Isolated analytes were treated with acetic anhydride/pyridine (1:1, v/v) to form less polar oligosaccharide derivatives, which could then be easily visualized and semi-quantitated using partition chromatography (thin later and paper) with chloroform/methanol. Structural identities of the purified oligosaccharides were determined using a combination of mass spectrometry and NMR (1H, 13C, HSQC, TOCSY, COSY, HMBC) techniques. Our results clearly demonstrate that the ethanol-based preservation, transport, and purification of oligosaccharides is a simple and robust method for the analysis of Rathi cow’s milk oligosaccharides. Furthermore, using the acetylation, purified oligosaccharides allow for rapid analysis on thin-layer chromatography, which is quite cost effective compared with other analytical methods.